(untitled) (Journal of Humanities, Social and Management Sciences (JHSMS-Asia), 2021)
The migration of Afghan refugees into Pakistan started in the wake of Saur (Red) Revolution in 1978, as a result of reforms introduced by the communist regime in Kabul, Afghanistan. However the large influx of refugees to Pakistan took place soon after the invasion of Soviet Union in 1979. Pakistan provided asylum for the approximately 4.2 million refugees. They were settled in 386 camps mostly in rural as well as in urban areas of the country. But the most populous province that has large number of Afghan refugees was Khyber Pakhtunkhwa (KP) (that time N.W.F.P), which has long border (Durand line) with Afghanistan, and also has cultural, religious, and linguistics ties. This large number of immigrants generated grave consequences for Pakistan, especially for Khyber Pakhtunkhwa. They have affected the socio-economic and political life of the province. The main objective of the study was to find out the socio-economic impact of Afghan Refugees living for more than three decades in the host society of KP. An empirical and analytical methodological approach was adopted for this study. To conclude the findings, the research reveals that that Afghan Refugees have not only affected the social set-up but also the economy of the local host society by introducing various type of social evils like begging, drugs culture, Kalashnikov culture (AK-47), Galemjum culture (prostitution) and corruption.